Controllable synthesis of nickel bicarbonate nanocrystals with high homogeneity for a high-performance supercapacitor. (24th July 2017) - Gu, Jianmin; Liu, Xin; Wang, Zhuang; Bian, Zhenpan; Jin, Cuihong; Sun, Xiao; Yin, Baipeng; Wu, Tianhui; Wang, Lin; Tang, Shoufeng; Wang, Hongchao; Gao, Faming
Abstract: The electrochemical performance of supercapacitors might be associated with the homogeneous structure of the electrode materials. However, the relationship between the degree of uniformity for the electrode materials and the electrochemical performance of the supercapacitor is not clear. Herein, we synthesize two types of nickel bicarbonate nanocrystals with different degrees of uniformity to investigate this relationship. As the electroactive material, the nickel bicarbonate nanocrystals with a homogeneous structure could provide a larger space and offer more exposed atoms for the electrochemical reaction than the nanocrystals with a heterogeneous structure. The homogeneous nickel bicarbonate nanocrystals exhibit better electrochemical performance and show excellent specific capacitance (1596 F g −1 at 2 A g −1 and 1260 F g −1 at 30 A g −1 ), which is approximately twice that of the heterogeneous nickel bicarbonate nanocrystals. The cycling stability for the homogeneity (∼80%) is higher than the inhomogeneity (∼61%) at a high current density of 5 A g −1 .